NIE Conference on Studies in Teaching Panel 7, Instructional Personnel Utilization - National Inst. of Education (DHEW), Washington, DC.; Gage, N. L.; National Inst. of Education (DHEW), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The goal of this panel was to generate scientific knowledge on how the organizational, administrative, physical, personal, and social aspects of the classroom, school, district, and community support instructional personnel in reaching educational goals. A matrix was developed using locational variables (within school and outside school) and operational variables (organizational/administrative, physical, and personal/social), to contain and display five "approaches" developed by the panel. The first approach dealt with the ways in which organizational and administrative aspects of the classroom and school can support instructional personnel in attaining educational goals. The second approach was concerned with the ways in which the organizational and administrative aspects of the school district and the community affect educational personnel in reaching educational goals. The third approach was concerned with the effects on staff functioning of the physical environment of the classroom and school. The fourth approach dealt with the ways in which personal and social aspects of the classroom and school aid staff in reaching educational goals. The fifth approach was concerned with similar informal social-personal influences outside the school or classroom context. Within these five approaches, 21 programs were formulated and rated as to their priority. (BD)
ERIC Note: For related documents, see SP 009 494-504.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrative Organization; Community Influence; Community Support; Educational Objectives; Environmental Influences; School Support; Social Influences; Teachers; Speeches/Meeting Papers